Solvent-induced dual-end-anchored durable polysiloxane coating, method of making and use thereof

CN122941307APending Publication Date: 2026-10-20XUZHOU UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611142150.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0006]然而,现有技术尚未将聚硅氧烷的溶剂响应构象变化与双端锚定过程有效结合,亦未见通过“第一溶剂体系促进链段相对舒展和第一端锚定-第二溶剂体系诱导链段塌缩或回折并促进第二端锚定”的两阶段溶剂诱导策略,在多种基底表面可控构筑双端锚定聚硅氧烷涂层的技术方案

Benefits of technology

1)本发明利用溶剂组成变化调控双端反应性聚硅氧烷链段构象,第一阶段通过第一溶剂体系促进链段舒展和第一端锚定,第二阶段通过第二溶剂体系诱导链段塌缩、回折或构象收缩并促进第二端锚定,从而提高双端锚定概率;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a solvent-induced, dual-end anchored durable polysiloxane coating, its preparation method, and its application. The method includes: activating a substrate surface to form an anchoring layer on the substrate surface that can bond with dual-end reactive polysiloxanes; placing the substrate with the anchoring layer in a first solvent system, allowing the dual-end reactive polysiloxane segments to maintain an extended conformation and causing initial anchoring of their first ends with the anchoring layer; switching the reaction system to a second solvent system, inducing the already anchored polysiloxane segments to collapse, fold back, or undergo conformational contraction, increasing the contact probability between the unreacted second end and the anchoring layer, and promoting further anchoring of the second end, thereby forming a polysiloxane coating rich in dual-end anchoring structures; by controlling the conformation of the polysiloxane segments through solvent composition, the effective contact probability between the unreacted end groups and the anchoring points is increased, thereby increasing the dual-end anchoring probability, and the resulting coating exhibits fluid-like interface characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional coating materials technology, specifically to a solvent-induced dual-end anchored durable polysiloxane coating, its preparation method, and its application. Background Technology

[0002] Low-adhesion, anti-fouling, and self-cleaning surfaces have significant application value in photovoltaic glass, solar module covers, architectural glass, display screen covers, sensor windows, polymer materials, and fluid transport components. Existing functional coatings typically achieve interface modulation through methods such as reducing surface energy, constructing micro / nano structures, grafting polymer brushes, or introducing lubricating layers. However, these methods are prone to problems such as insufficient adhesion, migration of functional components, performance degradation after scouring or friction, and aging failure during long-term use. For transparent substrates such as photovoltaic glass and solar module covers, functional coatings must simultaneously achieve low-fouling adhesion, self-cleaning, and high light transmittance. Therefore, the coating not only needs to reduce contaminant adhesion but also should avoid significantly adversely affecting visible light transmission.

[0003] Polysiloxanes, especially polydimethylsiloxanes, possess low surface energy, low glass transition temperature, compliant backbone, and good chemical stability. They exhibit segment migration and fluid-like characteristics at interfaces, making them suitable for constructing low-adhesion, low-friction, antifouling, and self-cleaning surfaces. Anchoring polysiloxane segments to the substrate surface can reduce interfacial adhesion of droplets, dust, particulate contaminants, and biological contaminants, making them easier to remove. Existing research shows that polymer chain topology significantly affects the wetting, antifouling, and tribological behavior of surfaces. For example, bi-terminated polysiloxane surfaces exhibit better hydrophobicity, self-cleaning, and droplet-slip properties compared to single-terminated or linear polysiloxane surfaces. However, existing methods for constructing bi-terminated polysiloxane surfaces often employ a single solvent system and a one-step grafting method. The segment conformation of the bi-terminated reactive polysiloxane during the reaction process and the probability of unreacted end groups approaching the substrate surface are difficult to control, resulting in a random formation of the bi-terminated anchoring structure. Therefore, there is still room for improvement in the degree of bi-terminated anchoring and coating durability.

[0004] Other studies have explored the construction of bi-terminal anchored polymer brush layers using block copolymers containing bi-terminal adhesion groups to improve surface antifouling and water-lubricating properties. For example, polyethylene glycol-based triblock copolymers containing bi-terminal catechol anchoring groups can be grafted onto the surface to form a bi-terminal anchored configuration, exhibiting superior antifouling and low-friction properties compared to single-terminal anchored polymers. However, these polymers typically require controlled polymerization methods such as atom transfer radical polymerization, involving steps such as monomer design, initiator preparation, oxygen-free polymerization, purification, and molecular weight control. The preparation process is complex and costly, hindering applications on large-area substrates and in industrial coatings. For commercially available or readily available bi-terminal reactive polysiloxanes, although both end groups can theoretically participate in surface anchoring, the conformation of the polysiloxane segments and the probability of unreacted end groups approaching the substrate surface are difficult to control in conventional one-step grafting or single-solvent systems, resulting in a often random bi-terminal anchoring process. In other words, the existing technology does not lack reactive end groups, but rather lacks a process control method that can increase the probability of effective contact between the unreacted second end and the surface anchoring point.

[0005] Polysiloxane segments exhibit significantly different solvation and conformational behaviors in different solvent environments. Polydimethylsiloxane tends to shrink or collapse in unfavorable solvents such as water, while it swells and expands more readily in organic solvents with better compatibility, exhibiting higher segment mobility. Therefore, by controlling the expansion, collapse, or folding state of polysiloxane segments through changes in solvent composition, the effective contact probability between unreacted end groups and anchoring points can be increased, providing a basis for improving the probability of double-end anchoring.

[0006] However, existing technologies have not effectively combined the solvent-responsive conformational changes of polysiloxanes with the double-end anchoring process, nor have they found a technical solution for controllably constructing double-end anchored polysiloxane coatings on various substrate surfaces through a two-stage solvent-induced strategy: "the first solvent system promotes relative chain extension and first-end anchoring, while the second solvent system induces chain collapse or folding back and promotes second-end anchoring." Therefore, there is an urgent need to develop a method for preparing polysiloxane functional coatings that is simple to process, requires no complex polymer synthesis, is applicable to various substrates, and can maintain low adhesion, self-cleaning, or low-friction properties after rinsing, immersion, or friction cycles. Summary of the Invention

[0007] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a solvent-induced, dual-end anchored durable polysiloxane coating, its preparation method, and its application. The core concept of this invention is to construct a reactive anchoring layer on the substrate surface and divide the grafting process of the dual-end reactive polysiloxane into two solvent-induced stages. The first stage uses a first solvent system, which is an alcohol-rich system, to keep the polysiloxane segments relatively extended or highly solvated in the solution, increasing the contact opportunity between the end groups and the anchoring points on the substrate surface, and achieving first-end anchoring. The second stage switches the solvent to a second solvent system, which is a water-rich system. Utilizing the conformational contraction effect of polysiloxane in this system, the polysiloxane segments that have already undergone first-end anchoring are induced to collapse, fold back, or undergo conformational contraction, making it easier for the unreacted second ends to approach the substrate surface and further anchor, thereby increasing the probability of dual-end anchoring and forming a stable dual-end anchored durable polysiloxane coating.

[0008] To achieve the above technical effects, the following technical solution is adopted: A method for preparing a solvent-induced, double-ended anchored durable polysiloxane coating includes the following steps: Step S1: Activate the substrate surface to form an anchoring layer on the substrate surface that can bond with the double-ended reactive polysiloxane; Step S2: Place the substrate with the anchoring layer obtained in step S1 into the first solvent system, add a double-ended reactive polysiloxane, and use the solvation regulation effect of the first solvent system on the double-ended reactive polysiloxane chain segments to make the double-ended reactive polysiloxane chain segments in a stretched state and make their first ends initially anchored to the anchoring layer. Step S3: Switch the reaction system in step S2 to the second solvent system. Utilize the conformational induction effect of the second solvent system on the polysiloxane segments that have undergone first-end anchoring to induce the polysiloxane segments to collapse, fold back, or conformationally shrink toward the anchoring layer, thereby increasing the contact probability between the second end and the anchoring layer and promoting further anchoring of the second end to form a polysiloxane coating rich in double-end anchoring structures. Step S4: Clean and dry the substrate obtained in step S3 to obtain the solvent-induced double-end anchored durable polysiloxane coating; Furthermore, the first solvent system is a solvent system that enables the two-terminal reactive polysiloxane segments to be in an extended state; the second solvent system is a solvent system that can induce the polysiloxane segments that have undergone first-terminal anchoring to collapse, fold back, or conformationally shrink. Furthermore, the first solvent system is an alcohol-rich system, and the second solvent system is a water-rich system; Furthermore, the first solvent system and the second solvent system are each independently water, an alcohol solvent, or a mixture of water and an alcohol solvent; wherein, the volume ratio of water to alcohol solvent in the first solvent system is 0:10 to 4:6, preferably 1:9 to 3:7; and the volume ratio of water to alcohol solvent in the second solvent system is 6:4 to 10:0, preferably 7:3 to 9:1. Furthermore, the alcohol solvent includes one or more of methanol, ethanol, isopropanol, n-propanol, and tert-butanol, preferably ethanol or isopropanol; Furthermore, the dual-terminated reactive polysiloxane includes one or more of the following: dual-terminated amino polydimethylsiloxane, dual-terminated hydroxyl polydimethylsiloxane, dual-terminated epoxy polydimethylsiloxane, dual-terminated carboxyl polydimethylsiloxane, dual-terminated mercapto polydimethylsiloxane, dual-terminated alkenyl polydimethylsiloxane, and dual-terminated alkynyl polydimethylsiloxane. Furthermore, the dual-terminated reactive polysiloxane is a dual-terminated amino polydimethylsiloxane with a molecular weight of 500-100000 Da, preferably 1000-50000 Da; Furthermore, the concentration of the dual-terminated reactive polysiloxane in the first solvent system is 0.01–100 mg / mL, preferably 0.1–50 mg / mL, and more preferably 1–20 mg / mL; Furthermore, the reaction temperature in step S2 is 10–80°C, and the reaction time is 5 min–48 h, preferably 0.5–2 h, more preferably 1 h; the reaction temperature in step S3 is 10–80°C, and the reaction time is 5 min–48 h, preferably 6–24 h, more preferably 12 h. Furthermore, the solvent switching method in step S3 is one or more of the following: direct displacement, gradient displacement, dropwise displacement, continuous flow displacement, soaking displacement, or cyclic displacement; Furthermore, the substrate includes one or more of the following: polymer material substrate, glass substrate, ceramic substrate, metal substrate, metal oxide substrate, silicon wafer substrate, or conductive oxide substrate; Furthermore, the polymer material substrate includes one or more of the following: polyvinyl chloride, polyurethane, polyethylene, polypropylene, polyethylene terephthalate, polycarbonate, polymethyl methacrylate, polyamide, polyimide, polytetrafluoroethylene, silicone rubber, natural rubber, and epoxy resin. Furthermore, the glass substrate includes one or more of the following: ordinary soda-lime glass, ultra-white rolled photovoltaic glass, ultra-white float photovoltaic glass, solar module cover glass, quartz glass, borosilicate glass, aluminosilicate glass, conductive coated glass, architectural glass, vehicle window glass, or display screen cover glass. Furthermore, when the substrate is a polymer material substrate, the activation treatment in step S1 is a dopamine oxidative self-polymerization deposition treatment, which forms a polydopamine adhesion layer on the surface of the polymer material substrate. Furthermore, in the dopamine oxidative self-polymerization deposition treatment, the dopamine concentration is 0.1–5 mg / mL, the buffer pH is 7.5–9.5, the deposition time is 5 min–24 h, preferably 12–24 h, more preferably 24 h, and the deposition temperature is 10–50 °C. Furthermore, when the substrate is a glass substrate, ceramic substrate, metal substrate, metal oxide substrate, silicon wafer substrate or conductive oxide substrate, the activation treatment in step S1 is one or more of the following: plasma treatment, ultraviolet ozone treatment, acid treatment, alkali treatment, peroxidation treatment, silica layer deposition treatment, silica sol treatment, tetraethyl orthosilicate hydrolysis condensation treatment, and reactive silane coupling agent grafting treatment. Furthermore, the reactive silane coupling agent includes one or more of the following: epoxy-containing silanes, isocyanate-containing silanes, aldehyde-containing silanes, acid anhydride-containing silanes, carboxyl-containing active ester-containing silanes, amino-containing silanes, and crosslinking agent composite systems. Furthermore, the epoxy-containing silane includes one or more of 3-glycidoxypropyltrimethoxysilane and 3-glycidoxypropyltriethoxysilane; the amino-containing silane includes one or more of 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane; and the crosslinking agent includes one or more of glutaraldehyde, genipin, and dialdehyde compounds. Furthermore, the dual-end anchoring structure refers to a fixed structure formed by both end groups of the same polysiloxane molecule being directly or indirectly bonded to the anchoring layer; the dual-end anchoring structure may include a ring structure and / or a bridging structure; Furthermore, the cleaning in step S4 includes washing with a second solvent system, a first solvent system, an alcohol solvent, water, n-hexane, cyclohexane, toluene, isopropanol, or a combination thereof to remove unanchored or weakly adsorbed polysiloxane molecules. The present invention also provides a solvent-induced dual-end anchored durable polysiloxane coating, the coating being prepared by the above method, the coating comprising an anchoring layer located on the surface of a substrate and a dual-end anchored durable polysiloxane layer located on the surface of the anchoring layer; Furthermore, the double-ended anchored durable polysiloxane layer has fluid-like interface characteristics, which can reduce the adhesion of water droplets to its surface and reduce interfacial friction and water droplet roll-off angle. Furthermore, the coating retains the polysiloxane surface characteristics even after water rinsing, friction cycling, long-term placement, chemical media treatment, or immersion treatment. Furthermore, when the substrate is a transparent glass substrate, the coating has an average transmittance of not less than 85% in the visible light range of 400–800 nm, preferably not less than 90%, and more preferably not less than 92%. This invention also provides the application of the above-mentioned solvent-induced double-ended anchored durable polysiloxane coating in low-adhesion, anti-fouling, self-cleaning, low-friction, erosion-resistant, transparent and anti-fouling surfaces; Furthermore, the coating is used on photovoltaic glass, solar module covers, architectural glass, vehicle window glass, display screen covers, sensor windows, transparent protective films, polymer films, polymer pipes, polymer sheets, fluid transport pipelines, microfluidic devices, ship surfaces, or antifouling component surfaces.

[0009] The beneficial effects of this invention are as follows: 1) This invention utilizes solvent composition changes to regulate the conformation of double-ended reactive polysiloxane segments. In the first stage, the first solvent system promotes segment extension and first-end anchoring. In the second stage, the second solvent system induces segment collapse, folding back, or conformational contraction and promotes second-end anchoring, thereby increasing the probability of double-ended anchoring. 2) This invention avoids the problem of existing double-end anchored polymer coatings relying on complex block copolymer synthesis. It does not require complex polymerization methods such as atom transfer radical polymerization. It can construct double-end anchored polysiloxane coatings using only commercially available or readily available double-end reactive polysiloxanes. 3) This invention differs from the random formation of double-end anchoring structures in a single solvent system. By controlling the conformation of polysiloxane segments through solvent switching paths, the effective contact probability between unreacted end groups and anchoring points is increased, making the double-end anchoring process more controllable. 4) The polysiloxane segments in the coating obtained by this invention have flexibility and fluid-like interface characteristics, which can reduce the adhesion and rolling resistance of water droplets on the coating surface and exhibit a low coefficient of friction in cyclic friction tests; on the surface of photovoltaic glass, the coating can also remove dust or mud contaminants with the help of rolling water droplets, thus achieving self-cleaning. 5) The coating obtained by the present invention improves the bonding stability between the polysiloxane layer and the substrate through double-end anchoring. Compared with single-end anchoring or physically adsorbed polysiloxane coatings, it has better erosion resistance, immersion resistance, friction cycle resistance and long-term stability. 6) The present invention can select different anchoring layers according to the substrate type. For polymer materials, a polydopamine adhesion layer can be used, and for glass and inorganic oxide substrates, a hydroxylated / silane coupling layer can be used. Therefore, it has good substrate compatibility and industrial application prospects. 7) In this invention, a transparent reactive silane coupling layer is preferably used as an anchoring layer on a transparent glass or photovoltaic glass substrate to avoid the adverse effect of the dark polydopamine layer on the light transmittance. This allows the resulting coating to maintain both high visible light transmittance and self-cleaning performance, making it suitable for transparent anti-fouling applications such as solar module covers. Attached Figure Description

[0010] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. The drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.

[0011] Figure 1 This is a schematic diagram illustrating the construction process of the solvent-induced double-ended anchored durable polysiloxane coating in an embodiment of the present invention. Figure 2 The first-stage grafting behavior of NH2-PDMS-NH2 on the surface of a polydopamine (PDA) modified substrate and the XPS characterization results are presented in the embodiments of the present invention. Figure 3 This is a diagram showing the consumption of quinone sites on the PDA surface during the first stage reaction in this embodiment of the invention. Figure 4 This illustrates the effect of the second-stage reaction time on the content of residual terminal amino groups on the sample surface in this embodiment of the invention. Figure 5 This illustrates the effect of the solvent composition in the second stage on the content of residual terminal amino groups in this embodiment of the invention. Figure 6 This is a comparison of the changes in the content of residual terminal amino groups on the surface of samples after the second stage treatment under different first-stage reaction time conditions in this embodiment of the invention. Figure 7 These are the test results of the coating water droplet roll-off angle under different reaction conditions in the embodiments of the present invention; Figure 8 This is a comparison of the placement stability of single-end anchored polysiloxane coatings and double-end anchored durable polysiloxane coatings in the embodiments of the present invention. Figure 9 This is a comparison of the water droplet roll-off angles of single-end anchored polysiloxane coatings and double-end anchored durable polysiloxane coatings under different chemical environments in this embodiment of the invention. Figure 10 The test results of the erosion resistance of the single-end anchored polysiloxane coating and the double-end anchored durable polysiloxane coating in the embodiments of the present invention are shown. Figure 11 The results show the changes in the friction coefficient of different samples during cyclic friction in the embodiments of the present invention; Figure 12 The results of Rhodamine 110 chloride fluorescent labeling of residual epoxy groups on the surface of photovoltaic glass at different processing stages in the embodiments of the present invention; Figure 13 This describes the water droplet rolling behavior of the double-ended anchored durable polysiloxane-coated photovoltaic glass in this embodiment of the invention. Figure 14 The transparency test results of the double-ended anchored durable polysiloxane coated photovoltaic glass in the embodiments of the present invention; Figure 15 These are the self-cleaning performance test results of the double-ended anchored durable polysiloxane coated photovoltaic glass in the embodiments of the present invention; Figure 16 This illustrates the impact of double-ended anchored durable polysiloxane-coated photovoltaic glass on the photoelectric output performance of solar cells in this embodiment of the invention. Figure 17 The variation in residual amine group density on the surface of the PDA-modified substrate in different water / alcohol solvent systems in the embodiments of the present invention is shown. Detailed Implementation

[0012] The present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Any equivalent substitutions, simple modifications or improvements made based on the technical concept of the present invention should be included within the scope of protection of the present invention.

[0013] Unless otherwise stated, all reagents used in the following examples are conventional reagents in the art, and all experimental methods used are conventional methods in the art. The volume ratios of water to ethanol or other alcohol solvents are all volume ratios, and all temperatures are reaction system temperatures.

[0014] The term "solvent-induced" in this invention refers to changing the solvation state, degree of expansion, degree of collapse, folding behavior, and effective contact probability between unreacted end groups and anchoring points of the double-ended reactive polysiloxane chain segments by altering the solvent composition, solvent polarity, or solvent selectivity of the reaction system, thereby promoting the formation of a double-ended anchoring structure.

[0015] The term "double-end anchoring" in this invention refers to the fact that both end groups of the same polysiloxane molecule are directly or indirectly bonded to the anchoring layer on the substrate surface, thereby allowing the polysiloxane chain segments to exist stably on the substrate surface in a double-end fixed manner. The double-end anchoring can manifest as a ring structure, a bridging structure, or a hybrid configuration of both.

[0016] The "fluid-like interface feature" referred to in this invention means that although the polysiloxane chain segments are anchored to the substrate surface through end groups, their main chain still maintains a certain degree of flexibility, chain segment migration, or interface rearrangement ability, thereby causing the coating surface to exhibit characteristics such as low adhesion, low friction, low slip angle, or easy desorption of contaminants. In the embodiments of this invention, the fluid-like interface feature is mainly manifested through a lower droplet roll-off angle, a lower coefficient of friction, better scouring stability, and self-cleaning effect.

[0017] Example 1: Preparation of solvent-induced double-end anchored durable polysiloxane coating on polymer substrate surface 1. Take a polyvinyl chloride (PVC) substrate, clean it with ethanol and deionized water in turn to remove surface oil and impurities, and dry it for later use.

[0018] 2. Prepare a dopamine hydrochloride solution with a dopamine concentration of 2 mg / mL and a Tris-HCl buffer solution at pH 8.5. Immerse the cleaned PVC substrate in the dopamine solution and react at room temperature for 24 h to allow dopamine to undergo oxidative self-polymerization deposition on the PVC substrate surface, forming a polydopamine adhesion layer.

[0019] 3. After the reaction is complete, remove the PVC substrate, wash it thoroughly with deionized water to remove unreacted dopamine and weakly adsorbed polydopamine particles, and dry it with nitrogen to obtain the PDA substrate.

[0020] 4. Prepare the first solvent system with a water-to-ethanol volume ratio of 1:9. Dissolve or disperse the diamino-terminated polydimethylsiloxane in the first solvent system to prepare a 10 mg / mL NH2-PDMS-NH2 solution. Immerse the PDA substrate in this solution and react for a certain time at room temperature to 40°C. During this stage, the NH2-PDMS-NH2 segments are in an extended state in the ethanol-rich system, and their terminal amino groups are more likely to approach the quinone groups or other reactive sites on the PDA layer surface, resulting in initial first-terminal anchoring.

[0021] 5. Replace the first solvent system in the reaction system with the second solvent system, in which the volume ratio of water to ethanol is 9:1, and continue the reaction for a certain period of time. During this stage, the NH2-PDMS-NH2 chain segments collapse, fold back, or undergo conformational contraction due to the change in solvent composition, causing the unreacted amino groups to approach the surface of the PDA layer and undergo second-end anchoring, forming a polysiloxane layer rich in double-end anchored structures.

[0022] 6. After the reaction is complete, the PVC substrate is washed sequentially with a mixture of ethanol / water and deionized water to remove unanchored or weakly adsorbed NH2-PDMS-NH2. Then, it is dried at room temperature or 40°C to obtain a solvent-induced double-end anchored durable polysiloxane coating on the surface of the PVC substrate.

[0023] Figure 1 This is a schematic diagram illustrating the construction process of the solvent-induced dual-end anchored durable polysiloxane coating in Example 1 of the present invention. In the first solvent system, the volume ratio of water to ethanol is 1:9. This system has a good solvation effect on the dual-amino-terminated polydimethylsiloxane segments, keeping the polysiloxane segments in a relatively extended state. This facilitates the approach of the first-terminal amino group to the quinone group or other reactive sites on the surface of the polydopamine layer and the initial anchoring. Subsequently, the reaction system is switched to the second solvent system, with a volume ratio of water to ethanol of 9:1. In a water-rich environment, the polysiloxane segments that have undergone first-end anchoring collapse, fold back, or conformational contraction, making it easier for the unreacted other-terminal amino group to approach the anchoring point on the PDA layer surface and react further, thereby forming a polysiloxane coating rich in dual-end anchored structures. Figure 1 The diagram also illustrates the difference in stability between single-end and double-end anchoring coatings under shear or scouring. The single-end anchoring chain segment is more prone to detachment under external force, while the double-end anchoring chain segment exhibits better structural stability because both ends are bonded to the anchoring layer.

[0024] To confirm that NH2-PDMS-NH2 can be effectively introduced into the PDA surface in the first stage, its grafting process and surface chemical composition were characterized. The first-stage grafting process was monitored in situ using a quartz crystal microbalance, and the surface chemical composition after grafting was characterized using XPS. The results are as follows: Figure 2 As shown, with the extension of the first-stage reaction time, the surface grafting quality gradually increases and tends to stabilize after a certain time, indicating that NH2-PDMS-NH2 can gradually bind to the PDA layer surface in the first solvent system. XPS peak analysis results show that peaks such as CH / CC, C-OH / CN, and C=O can be observed in the PDA-modified surface; C-Si and other polysiloxane-related characteristic peaks appear in the surface treated with NH2-PDMS-NH2, indicating that NH2-PDMS-NH2 has been successfully introduced into the PDA-PVC substrate surface.

[0025] The effect of the first-stage reaction time on the consumption of PDA reaction sites was further investigated. The content of quinone sites in the PDA layer under different first-stage reaction times was measured, and the results are as follows: Figure 3As shown, with the extension of the first-stage reaction time, the quinone-related signal on the PDA layer surface gradually decreased, indicating that the quinone sites in the PDA layer that can react with the terminal amino groups were gradually consumed, meaning that the terminal amino groups of NH2-PDMS-NH2 reacted with the PDA layer. This result indicates that the first-stage reaction time needs to strike a balance between "ensuring the initial anchoring quantity" and "retaining reaction sites available for further second-stage anchoring." If the reaction time is too short, the initial anchoring quantity of NH2-PDMS-NH2 is insufficient; if the reaction time is too long, the reaction sites on the PDA layer surface available for further second-stage anchoring may be excessively consumed. Therefore, the optimal first-stage reaction time cannot be directly determined based solely on the quinone consumption results of the first stage; further judgment is needed by considering the residual terminal amino group content after the second-stage induction treatment.

[0026] To investigate the effect of the second-stage solvent-induced treatment time on the content of residual terminal amino groups, samples after the first-stage initial anchoring treatment were selected and reacted in the second solvent system for different times. The content of residual terminal amino groups on the sample surface was then measured. The results are as follows: Figure 4 As shown, with the extension of the second-stage reaction time, the content of residual terminal amino groups on the sample surface decreased significantly and tended to stabilize after about 12 hours. This result indicates that the water-rich system in the second stage can promote the further participation of unreacted terminal amino groups in the anchoring reaction, and that when the second-stage reaction time is 12 hours, the further consumption of terminal amino groups has basically reached a stable state. Therefore, in subsequent experiments, the preferred second-stage reaction time is 12 hours.

[0027] To further verify whether the decrease in the content of residual terminal amino groups in the second stage originated from the inducing effect of the water-rich second solvent system, rather than simply from extending the reaction time, a control experiment without switching solvents was set up, and the results are as follows: Figure 5As shown in the figure. Specifically, a PDA-modified PVC substrate was placed in a first solvent system containing 10 mg / mL NH2-PDMS-NH2 at a water / ethanol volume ratio of 1:9 and reacted for 1 h to obtain a one-end anchored sample. The sample had a high content of residual terminal amino groups on its surface, indicating that NH2-PDMS-NH2 had been introduced into the PDA layer surface, while its unreacted terminal amino groups remained exposed on the coating surface. Subsequently, the one-end anchored samples were divided into two groups for control treatment: one group was cleaned and treated in an ethanol-rich system with a water / ethanol volume ratio of 1:9 for 12 h, as the ethanol-rich extended treatment group; the other group was cleaned and then treated in a second water-rich solvent system with a water / ethanol volume ratio of 9:1 for 12 h, as the water-rich induction treatment group. The results showed that the content of residual terminal amino groups in the ethanol-rich extended treatment group remained at a high level, with only a limited decrease compared to the one-end anchored samples, indicating that without changing the solvent composition, simply extending the reaction time is not effective in promoting further anchoring of unreacted terminal amino groups. In contrast, the residual terminal amino content in the water-rich induced treatment group was significantly reduced, indicating that the water-rich second solvent system can induce the collapse, foldback, or conformational contraction of the NH2-PDMS-NH2 chain segments that have undergone first-end anchoring, making it easier for unreacted terminal amino groups to approach the reaction sites on the PDA layer surface and further participate in the anchoring reaction. These results indicate that the higher residual terminal amino content in the one-end anchored sample originates from the retention of unreacted terminal amino groups after the first-stage grafting; while the significant reduction in residual terminal amino groups after treatment with the water-rich second solvent system indicates that the second-stage treatment promotes further consumption of unreacted terminal amino groups and the formation of a double-end anchored structure. The ethanol-rich extended treatment group did not show a similar degree of amino group reduction, further demonstrating that the enhanced double-end anchoring effect of this invention mainly originates from the chain segment conformational changes induced by the water-rich solvent switching, rather than simply the extension of reaction time.

[0028] After determining the second-stage reaction time to be 12 h, samples obtained from the first-stage reaction at 0.5 h, 1 h, 1.5 h, and 2 h were further selected and reacted in the second solvent system for another 12 h to obtain the corresponding double-end anchored samples. The residual terminal amino content on the sample surface before and after the second-stage treatment was detected, and the results are as follows: Figure 6As shown in the figure, PDA is a polydopamine-modified substrate, and PDA-12 is a control sample of PDA substrate treated with the second solvent system for 12 h. S0.5, S1, S1.5, and S2 represent the initial first-end anchored samples obtained by reacting in the first solvent system for 0.5 h, 1 h, 1.5 h, and 2 h, respectively. S0.5-D, S1-D, S1.5-D, and S2-D represent the double-end anchored samples obtained by further switching the above samples to the second solvent system for another 12 h. The results show that after the first stage treatment, the content of residual terminal amino groups on the sample surface increases with the extension of reaction time, indicating that the grafting amount of NH2-PDMS-NH2 on the PDA layer surface gradually increases. After the second stage treatment, the content of residual terminal amino groups on the surface of each sample is significantly reduced, indicating that the second stage solvent-induced treatment promotes the further reaction between unreacted terminal amino groups and anchoring sites on the PDA layer surface. Among them, the sample after the first stage reaction for 1 h and the second stage treatment for 12 h had a low residual terminal amino content, indicating that the second end anchoring was sufficient under the conditions, which is conducive to the formation of a stable double-end anchored durable polysiloxane layer.

[0029] Further tests were conducted on the water droplet rolling angle of samples with different first-stage reaction times and after the second-stage treatment. The results are as follows: Figure 7 As shown, different reaction times in the first stage affect the droplet low-adhesion performance of the resulting coating; among them, the sample with a first-stage reaction time of 1 h followed by a second-stage treatment of 12 h exhibited a lower droplet roll-off angle, indicating that the polysiloxane interface formed under these conditions is more conducive to reducing droplet adhesion. Combined with... Figures 3 to 6 The results show that the first-stage reaction time of 1 hour can provide sufficient initial anchoring quantity and retain a certain number of PDA reaction sites for further anchoring at the second end. Therefore, it can be used as the preferred first-stage reaction time in this embodiment.

[0030] To evaluate the impact of the double-ended anchoring structure on the long-term stability of the coating, a placement stability test was conducted on a single-ended anchored polysiloxane coating and the double-ended anchored durable polysiloxane coating obtained in this invention. The results are as follows: Figure 8 As shown, with prolonged placement time, the water droplet roll-off angle of the single-end anchored polysiloxane coating gradually increases, indicating a decline in its low-adhesion performance. In contrast, the double-end anchored polysiloxane coating obtained in this invention maintains a lower water droplet roll-off angle under the same placement conditions, demonstrating that the double-end anchoring structure is beneficial for improving the long-term stability of the polysiloxane coating.

[0031] To evaluate the low-adhesion stability of the coatings under different chemical environments, single-end anchored polysiloxane coatings and double-end anchored durable polysiloxane coatings were immersed in four liquids for 24 h: pH 6.5 and pH 7.4 physiological buffer solutions, 0.1 wt% sodium dodecyl sulfate solution (SDS), and 0.9 wt% physiological saline. The changes in the water droplet roll-off angle of the coatings after different environmental treatments were tested. The results are as follows: Figure 9 As shown, under the aforementioned different environmental conditions, the droplet roll-off angle of the single-end anchored polysiloxane coating is significantly higher than that of the double-end anchored polysiloxane coating. In contrast, the double-end anchored polysiloxane coating maintains a lower droplet roll-off angle in different solution systems, indicating that the double-end anchoring structure can improve the interfacial stability and resistance to environmental disturbances of the coating.

[0032] To further evaluate the stability of the double-ended anchored structure under external force, the single-ended anchored polysiloxane coating and the double-ended anchored polysiloxane coating were subjected to shearing or scouring treatment, respectively, and the change in the water droplet roll-off angle after treatment was tested. The results are as follows: Figure 10 As shown, with increasing shear or erosion intensity, the droplet roll-off angle of the single-end anchored polysiloxane coating increases significantly, indicating that its low surface adhesion properties are compromised; while the double-end anchored durable polysiloxane coating maintains a lower droplet roll-off angle under the same conditions, indicating that the double-end anchoring structure can reduce the desorption of polysiloxane segments under external force, thereby improving the coating's shear and erosion resistance stability.

[0033] The friction resistance stability of the coating was further evaluated using a cyclic friction method, and the results are as follows: Figure 11 As shown, the PVC substrate and PDA-modified PVC substrate exhibited high coefficients of friction during cyclic friction. The single-end anchored polysiloxane coating initially had a low coefficient of friction, but its coefficient gradually increased with the number of friction cycles, indicating that the single-end anchored segments were prone to desorption or interfacial structural damage under friction. In contrast, the double-end anchored durable polysiloxane coating obtained in this invention maintained a consistently low and stable coefficient of friction during cyclic friction, with an average coefficient of friction lower than that of the single-end anchored polysiloxane coating, the PDA-modified PVC substrate, and the untreated PVC substrate. These results demonstrate that the double-end anchoring structure can improve the interfacial stability of the polysiloxane coating, enabling it to maintain excellent low-friction performance during cyclic friction.

[0034] In summary, Example 1 demonstrates that the first solvent system promotes the expansion of NH2-PDMS-NH2 segments and initial anchoring at the first end, while the second solvent system induces the collapse or folding back of the polysiloxane segments that have already undergone initial anchoring and promotes further anchoring at the second end. By controlling the reaction time of the first and second stages, a durable polysiloxane coating with double-ended anchoring can be obtained on the PVC substrate surface, exhibiting low adhesion, low water droplet roll-off angle, good placement stability, resistance to environmental disturbances, erosion resistance, and abrasion resistance.

[0035] Example 2: Preparation of Solvent-Induced Double-Ended Anchored Durable Polysiloxane Self-Cleaning Coating on Photovoltaic Glass Surface This embodiment illustrates the application of the present invention on transparent inorganic substrates, particularly photovoltaic glass and cover glass for solar modules. Unlike Example 1, which uses a PDA layer as the polymer substrate anchoring layer, this embodiment uses a transparent epoxy silane coupling layer as the anchoring layer to balance reactive anchoring and optical transparency.

[0036] 1. Take a photovoltaic glass sheet and clean it in sequence with detergent, deionized water, ethanol and deionized water, and then dry it for later use.

[0037] 2. Place the photovoltaic glass sheet in an oxygen plasma treatment device for 5 minutes or in an ultraviolet ozone device for 20 minutes to increase the hydroxyl density on the glass surface and obtain hydroxylated photovoltaic glass.

[0038] 3. Prepare a silanization solution containing 3-glycidoxypropyltrimethoxysilane. Immerse the hydroxylated photovoltaic glass in the silanization solution and react for 1 hour to allow the silane coupling agent to undergo hydrolysis and condensation with the hydroxyl groups on the glass surface, forming a reactive silane coupling layer containing epoxy groups on the surface.

[0039] 4. After the reaction is complete, remove the photovoltaic glass sheet, clean it with ethanol, and heat-treat it at 60°C for 20 min to enhance the bonding stability between the silane coupling layer and the photovoltaic glass substrate.

[0040] 5. Prepare the first solvent system with a water to ethanol volume ratio of 1:9. Add NH2-PDMS-NH2 to the system at a concentration of 10 mg / mL. Immerse the photovoltaic glass with an epoxy silane coupling layer on its surface into this solution and react for 1 h at room temperature to 60°C. This allows the NH2-PDMS-NH2 segments to unfold in the ethanol-rich system, and the first terminal amino group to undergo a ring-opening reaction with the epoxy group, achieving initial anchoring.

[0041] 6. Switch the first solvent system to a second solvent system with a water to ethanol volume ratio of 9:1, and continue the reaction for 12 h to induce the collapse or folding back of the polysiloxane chain segments, so that the unreacted terminal amino groups approach the glass surface and react further with the remaining epoxy groups, thereby forming a double-ended anchored polysiloxane coating.

[0042] 7. After the reaction is complete, the photovoltaic glass is washed with ethanol and deionized water in sequence to remove unanchored polysiloxane molecules. After drying, a solvent-induced double-end anchored durable polysiloxane self-cleaning coating is obtained on the surface of the photovoltaic glass.

[0043] To investigate the applicability of the solvent-induced dual-end anchoring strategy described in this invention to the surface of transparent photovoltaic glass, and to further confirm that the transparent epoxy silane coupling layer can serve as a reactive anchoring layer for NH2-PDMS-NH2, this embodiment performs fluorescent labeling analysis on the residual epoxy group content on the sample surface at different treatment stages. Since the terminal amino groups of NH2-PDMS-NH2 can undergo ring-opening reactions with the epoxy groups in the epoxy anchoring layer, the change in the residual epoxy group content on the sample surface can reflect the degree to which the terminal amino groups of NH2-PDMS-NH2 consume the epoxy anchoring sites. If the residual epoxy groups are further reduced after the second stage of treatment, it indicates that the water-rich second solvent system can promote the initially anchored polysiloxane segments to move closer to the glass surface and allow unreacted terminal amino groups to continue participating in the anchoring reaction. Specifically, Rhodamine 110 chloride is used as an amino fluorescent probe, whose amino groups can undergo ring-opening reactions with the residual epoxy groups on the sample surface. After washing away unreacted or physically adsorbed Rhodamine, the fluorescence intensity on the sample surface is detected to characterize the relative content of residual epoxy anchoring sites. like Figure 12As shown, the epoxy glass is a photovoltaic glass with an epoxy anchoring layer formed after hydroxylation and treatment with 3-glycidyl etheroxypropyltrimethoxysilane; the solvent control is a sample of epoxy glass treated with a second solvent system; one-end anchoring is a sample after NH2-PDMS-NH2 initially anchors to the epoxy anchoring layer in the first solvent system; and double-end anchoring is a sample with a double-end anchored polysiloxane coating obtained after the one-end anchored sample is further induced by the second solvent system. The results showed that the epoxy glass had high fluorescence intensity, indicating that a reactive silane coupling layer containing epoxy groups was successfully formed on the surface of the photovoltaic glass. The fluorescence intensity of the epoxy glass treated with the second solvent system changed little, indicating that the second solvent system itself did not significantly consume the epoxy anchoring sites. The fluorescence intensity of the initially anchored sample in the first stage decreased significantly, indicating that the terminal amino group of NH2-PDMS-NH2 underwent a ring-opening reaction with some epoxy groups. The fluorescence intensity of the solvent-induced double-ended anchored sample in the second stage further decreased, indicating that the water-rich second solvent system could induce the collapse, foldback, or conformational contraction of the initially anchored polysiloxane segments, making it easier for the unreacted terminal amino groups to approach and further consume the remaining epoxy anchoring sites on the surface of the photovoltaic glass, thereby facilitating the formation of a double-ended anchored polysiloxane coating.

[0044] The water droplet adhesion properties of the coated surface were tested. A certain volume of water droplets was added to the surface of an inclined sample, and the rolling behavior of the water droplets on the sample surface was observed. Figure 13 As shown, the untreated photovoltaic glass surface exhibits a certain degree of adhesion and pinning effect on water droplets, making it difficult for them to roll off quickly. In contrast, water droplets on the double-ended anchored polysiloxane coating surface can roll away rapidly. This result indicates that the compliant polysiloxane segments on the coating surface can reduce the interfacial adhesion and sliding resistance between water droplets and the glass surface, thereby endowing photovoltaic glass with low adhesion and easy-to-clean properties.

[0045] Secondly, the optical transparency of the coated samples was tested. The transmittance in the visible light range of untreated photovoltaic glass and double-ended anchored durable polysiloxane coated photovoltaic glass was measured using a UV-Vis spectrophotometer. For example... Figure 14 As shown, the double-ended anchored durable polysiloxane coated photovoltaic glass still maintains high transmittance in the visible light region. Its transmittance curve is basically close to that of the untreated photovoltaic glass, indicating that the coating is thin and has good transparency, and will not have a significant adverse effect on the visible light transmittance of the photovoltaic glass.

[0046] Furthermore, the self-cleaning performance of the coated samples was evaluated. Simulated dust or mud contaminants were uniformly spread on the surfaces of untreated photovoltaic glass and double-ended anchored polysiloxane-coated photovoltaic glass, and then a rainwater cleaning process was simulated by rinsing with water droplets. Figure 15As shown, contaminants on the untreated photovoltaic glass surface adhere strongly to the substrate, making it difficult for water droplets to form a continuous sliding path on the surface. The contaminants mainly remain in their original area, with only a small number of particles being carried away locally, leaving noticeable residue on the surface. In contrast, water droplets on the double-ended anchored polysiloxane coating surface can slide rapidly along the inclined direction, forming a clear cleaning channel during the movement. Contaminants in the area indicated by the red arrow are effectively carried away from the glass surface by the water droplets, significantly reducing the contamination coverage area. These results demonstrate that the coating obtained in Example 2 can reduce the adhesion of particulate contaminants such as dust and dirt to the photovoltaic glass surface, facilitating the removal of contaminants from the surface by rainwater or washing water, thereby achieving self-cleaning of the photovoltaic glass.

[0047] Finally, untreated photovoltaic glass and double-ended anchored durable polysiloxane-coated photovoltaic glass were respectively applied to the surface of solar cells, and their photoelectric conversion performance was tested. Figure 16 As shown, the solar cells covered with photovoltaic glass featuring a double-ended anchored durable polysiloxane coating still maintain similar current density-voltage output characteristics to the untreated photovoltaic glass, indicating that the transparent self-cleaning coating does not significantly weaken incident light transmission and cell output performance. Because this coating reduces contaminant adhesion and promotes rainwater-carried dust roll-off, it helps reduce light flux loss caused by dust obstruction in polluted environments or outdoor use conditions, thereby contributing to maintaining the photoelectric conversion efficiency and long-term power generation stability of the photovoltaic module.

[0048] The above results indicate that the solvent-induced double-ended anchored polysiloxane coating on the photovoltaic glass surface obtained in Example 2 has low water droplet adhesion, high transparency, self-cleaning properties, and good photovoltaic compatibility, making it suitable for photovoltaic glass, solar module covers, and other transparent anti-fouling surfaces.

[0049] Example 3: Preparation of solvent-induced double-end anchored durable polysiloxane coating in isopropanol / water system To demonstrate that the solvent-induced dual-end anchoring strategy described in this invention is not limited to the ethanol / water system, this embodiment uses isopropanol instead of ethanol to construct an isopropanol / water mixed solvent system, and prepares a dual-end anchored polysiloxane coating on the surface of a polydopamine-modified polymer substrate. This embodiment is mainly used to verify the applicability and substitutability of different water / alcohol mixed solvent systems for the dual-end anchoring process.

[0050] 1. Take a polyvinyl chloride base, clean it with ethanol and deionized water in turn to remove surface oil and impurities, and dry it for later use.

[0051] 2. Prepare a dopamine hydrochloride solution with a dopamine concentration of 2 mg / mL and a Tris-HCl buffer solution at pH 8.5. Immerse the cleaned polyvinyl chloride substrate in the dopamine solution and react at room temperature for 2 hours to allow dopamine to undergo oxidative self-polymerization deposition on the surface of the polyvinyl chloride substrate, forming a polydopamine adhesion layer.

[0052] 3. After the reaction is complete, remove the polyvinyl chloride substrate and wash it thoroughly with deionized water to remove unreacted dopamine and weakly adsorbed polydopamine particles. Then dry it with nitrogen to obtain polydopamine-modified polyvinyl chloride substrate.

[0053] 4. Prepare a first solvent system, which is a mixture of water and isopropanol, wherein the volume ratio of water to isopropanol is 1:9. Add diamino-terminated polydimethylsiloxane to the first solvent system to prepare a diamino-terminated polydimethylsiloxane solution with a concentration of 10 mg / mL.

[0054] 5. Immerse the polydopamine-modified polyvinyl chloride substrate obtained in step 3 into the diamino-terminated polydimethylsiloxane solution obtained in step 4, and react for 1 h at room temperature to 40°C. During this stage, the first solvent system, with a higher proportion of isopropanol, provides a relatively high solvation environment for the polysiloxane segments, allowing the diamino-terminated polydimethylsiloxane segments to be in a relatively extended or swollen state, and enabling the first-terminal amino groups to initially anchor to the quinone groups in the polydopamine layer.

[0055] 6. Replace the first solvent system in the reaction system with a second solvent system, which is a mixture of water and isopropanol, with a water-to-isopropanol volume ratio of 9:1, and continue the reaction for 12 hours. In this stage, the higher water content of the second solvent system reduces the solvation degree of the polysiloxane segments, inducing the collapse, folding back, or conformational contraction of the polysiloxane segments that have already undergone first-end anchoring. This causes the unreacted amino groups to approach the anchoring points on the surface of the polydopamine layer and promotes further second-end anchoring, thereby forming a polysiloxane layer rich in double-end anchoring structures.

[0056] 7. After the reaction is complete, the polyvinyl chloride substrate is washed sequentially with isopropanol / water mixed solvent and deionized water to remove unanchored or weakly adsorbed double-ended amino polydimethylsiloxane molecules; then dried at room temperature or 40°C to obtain a solvent-induced double-ended anchored durable polysiloxane coating on the surface of the polyvinyl chloride substrate.

[0057] To investigate the feasibility of using an isopropanol / water system as a substitute for an ethanol / water system in a solvent-induced biaxial anchoring process, the amino group density on the surface of samples at different treatment stages was measured. The results are as follows: Figure 17As shown, the single-end anchored samples are those obtained after reacting the PDA-modified substrate in either a water / ethanol (volume ratio 1:9) or water / isopropanol (volume ratio 1:9) solvent system containing NH2-PDMS-NH2 for 1 h. The double-end anchored samples are those obtained after further treating the single-end anchored samples in their respective water-rich second solvent systems for 12 h, with the ethanol / water system volume ratio being 1:9 and the isopropanol / water system volume ratio being 1:9. After the first stage of reaction, the single-end anchored samples obtained in both the water / ethanol and water / isopropanol systems exhibited high residual amine group densities, indicating that NH2-PDMS-NH2 can be introduced onto the surface of the PDA-modified substrate in both alcohol-rich first solvent systems, and its unreacted terminal amino groups remain exposed on the coating surface. The amine group densities of the single-end anchored samples in the two systems are relatively similar, indicating that both the isopropanol / water and ethanol / water first solvent systems can achieve initial anchoring of NH2-PDMS-NH2. After the second stage of water-rich system treatment, the residual amine density of the double-ended anchored samples obtained from the water / ethanol system and the water / isopropanol system was significantly lower than that of the corresponding single-ended anchored samples. This indicates that the water-rich second solvent system can induce the initial anchored NH2-PDMS-NH2 chain segments to collapse, fold back, or conformationally shrink, allowing the unreacted terminal amino groups to move closer to the reaction sites on the PDA layer surface and participate in the anchoring reaction, thereby reducing the surface residual amine density.

[0058] The above results indicate that the water / isopropanol system and the water / ethanol system exhibit similar trends during both one-end and two-end anchoring processes, achieving initial anchoring in the first stage and further consumption of the residual terminal amino groups in the second stage. This suggests that isopropanol can replace ethanol in constructing water / alcohol mixed solvent-induced systems, and the solvent-induced two-end anchoring strategy described in this invention is not limited to the ethanol / water system.

[0059] Mechanism of action explanation: The core mechanism of this invention lies in changing the conformational state of the dual-end reactive polysiloxane segments in solution through a two-stage solvent system, thereby increasing their dual-end anchoring probability.

[0060] In the first stage, the alcohol-rich system, especially the ethanol-rich system, has a good solvation effect on the polysiloxane chain segment, which makes the NH2-PDMS-NH2 molecular chain relatively extended in the solution. Its terminal amino groups are more likely to approach the PDA layer, epoxy silane layer, aldehyde silane layer or other reactive anchoring sites on the substrate surface and undergo the first end anchoring.

[0061] In the second stage, after the system switches to a water-rich environment, the polysiloxane segments tend to collapse, fold back, or undergo conformational contraction, bringing the unreacted end group closer to the substrate surface. At this point, the contact probability between the second end group and the remaining anchoring points on the substrate surface increases, thereby promoting second-end anchoring. Through this stretching-collapse or stretching-folding process, a double-end anchored durable polysiloxane layer can be formed on the substrate surface.

[0062] Compared with single-end anchoring structures, double-end anchoring structures can reduce the risk of overall desorption of polysiloxane chain segments during water flow scouring, friction, immersion, or aging. Compared with highly cross-linked rigid coatings, the polysiloxane backbone of the present invention still maintains flexibility and a certain chain segment mobility, thus exhibiting fluid-like interface characteristics and reducing interface adhesion and friction.

[0063] The preparation method of this invention features mild conditions, simple process, strong substrate adaptability, and easy scale-up. It can be applied to substrates with different morphologies through dip coating, spraying, drop coating, flow treatment, or continuous processing. For polymer materials, this invention can provide a universal adhesion interface through a polydopamine layer; for glass substrates, this invention can provide reactive anchoring sites through hydroxylation and transparent silane coupling layers, thereby avoiding the influence of a dark underlying layer on transparency. The chemical composition of different anchoring layers may differ, but their common function is to provide surface anchoring sites for the double-ended reactive polysiloxanes to bond with. Therefore, they are all specific embodiments under the same solvent-induced double-ended anchoring technology concept of this invention.

[0064] In particular, when the glass substrate is photovoltaic glass or solar module cover glass, the coating obtained by the present invention can reduce the adhesion of dust, dirt and particulate pollutants to the glass surface while maintaining transparency, and reduce the sliding resistance of water droplets, making it easier for rainwater or washing water to carry pollutants away from the glass surface, thereby achieving self-cleaning of photovoltaic glass and helping to maintain the solar transmittance efficiency.

[0065] The coating obtained by this invention can be widely used in self-cleaning photovoltaic glass, transparent anti-fouling surfaces, architectural glass, automotive window glass, display screen covers, sensor windows, polymer films, polymer pipes, fluid transport components, anti-fouling components, and other fields that require low adhesion, low friction, and durable surfaces, and has good prospects for industrial application.

[0066] Therefore, those skilled in the art will recognize that although embodiments of the present invention have been shown and described in detail herein, many other variations or modifications conforming to the principles of the present invention can be directly determined or derived from the disclosure of the present invention without departing from the spirit and scope of the invention. Therefore, the scope of the present invention should be understood and recognized as covering all such other variations or modifications.

Claims

1. A method for preparing a solvent-induced, double-ended anchored durable polysiloxane coating, characterized in that, The preparation method includes the following steps: Step S1: Activate the substrate surface to form an anchoring layer on the substrate surface that can bond with the double-ended reactive polysiloxane; Step S2: Place the substrate with the anchoring layer obtained in step S1 into the first solvent system, add a double-ended reactive polysiloxane, and use the solvation regulation effect of the first solvent system on the double-ended reactive polysiloxane chain segments to make the double-ended reactive polysiloxane chain segments in a stretched state and make their first ends initially anchored to the anchoring layer. Step S3: Switch the reaction system in step S2 to the second solvent system. Utilize the conformational induction effect of the second solvent system on the polysiloxane segments that have undergone first-end anchoring to induce the polysiloxane segments to collapse, fold back, or conformationally shrink toward the anchoring layer, thereby increasing the contact probability between the second end and the anchoring layer and promoting further anchoring of the second end to form a polysiloxane coating rich in double-end anchoring structures. Step S4: Clean and dry the substrate obtained in step S3 to obtain the solvent-induced double-ended anchored durable polysiloxane coating.

2. The method for preparing a solvent-induced, double-ended anchored durable polysiloxane coating as described in claim 1, characterized in that, The first solvent system and the second solvent system are each independently water, an alcohol solvent, or a mixture of water and an alcohol solvent; wherein, the volume ratio of water to alcohol solvent in the first solvent system is 0:10 to 4:6; the volume ratio of water to alcohol solvent in the second solvent system is 6:4 to 10:0; the alcohol solvent includes one or more of methanol, ethanol, isopropanol, n-propanol, and tert-butanol.

3. The method for preparing a solvent-induced, double-ended anchored durable polysiloxane coating as described in claim 1, characterized in that, The dual-terminated reactive polysiloxane includes one or more of the following: dual-terminated amino polydimethylsiloxane, dual-terminated hydroxyl polydimethylsiloxane, dual-terminated epoxy polydimethylsiloxane, dual-terminated carboxyl polydimethylsiloxane, dual-terminated mercapto polydimethylsiloxane, dual-terminated alkenyl polydimethylsiloxane, and dual-terminated alkynyl polydimethylsiloxane. The concentration of the dual-terminated reactive polysiloxane in the first solvent system is 0.01–100 mg / mL.

4. The method for preparing a solvent-induced, double-ended anchored durable polysiloxane coating as described in claim 1, characterized in that, The reaction temperature in step S2 is 10–80℃ and the reaction time is 5 min–48 h; the reaction temperature in step S3 is 10–80℃ and the reaction time is 5 min–48 h.

5. The method for preparing a solvent-induced, double-ended anchored durable polysiloxane coating as described in claim 1, characterized in that, The substrate includes one or more of the following: polymer material substrate, glass substrate, ceramic substrate, metal substrate, metal oxide substrate, silicon wafer substrate, or conductive oxide substrate; the polymer material substrate includes one or more of the following: polyvinyl chloride, polyurethane, polyethylene, polypropylene, polyethylene terephthalate, polycarbonate, polymethyl methacrylate, polyamide, polyimide, polytetrafluoroethylene, silicone rubber, natural rubber, and epoxy resin; the glass substrate includes one or more of the following: ordinary soda-lime glass, ultra-white rolled photovoltaic glass, ultra-white float photovoltaic glass, solar module cover glass, quartz glass, borosilicate glass, aluminosilicate glass, conductive coated glass, architectural glass, automotive window glass, or display screen cover glass.

6. The method for preparing a solvent-induced, double-ended anchored durable polysiloxane coating as described in claim 5, characterized in that, When the substrate is a polymer material substrate, the activation treatment in step S1 is a dopamine oxidative self-polymerization deposition treatment, which forms a polydopamine adhesion layer on the surface of the polymer material substrate. The dopamine concentration is 0.1-5 mg / mL, the buffer pH is 7.5-9.5, the deposition time is 5 min-24 h, and the deposition temperature is 10-50℃. When the substrate is a glass substrate, ceramic substrate, metal substrate, metal oxide substrate, silicon wafer substrate, or conductive oxide substrate, the activation treatment in step S1 is one or more of the following: plasma treatment, ultraviolet ozone treatment, acid treatment, alkali treatment, peroxidation treatment, silica layer deposition treatment, silica sol treatment, tetraethyl orthosilicate hydrolysis condensation treatment, and reactive silane coupling agent grafting treatment.

7. The method for preparing a solvent-induced, double-ended anchored durable polysiloxane coating as described in claim 6, characterized in that, The reactive silane coupling agent includes one or more of the following: epoxy-containing silanes, isocyanate-containing silanes, aldehyde-containing silanes, anhydride-containing silanes, carboxyl-containing reactive ester-containing silanes, amino-containing silanes, and crosslinking agent composite systems; the epoxy-containing silane includes one or more of 3-glycidoxypropyltrimethoxysilane and 3-glycidoxypropyltriethoxysilane; the amino-containing silane includes one or more of 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane; and the crosslinking agent includes one or more of glutaraldehyde, genipin, and dialdehyde compounds.

8. A solvent-induced, double-ended anchored, durable polysiloxane coating, characterized in that, The coating is prepared by the preparation method according to any one of claims 1 to 7, and the coating includes an anchoring layer on the surface of the substrate and a double-ended anchored polysiloxane layer on the surface of the anchoring layer; the double-ended anchored polysiloxane layer has fluid-like interface characteristics, which can reduce the adhesion of water droplets on its surface, reduce interfacial friction and water droplet roll-off angle. The coating retains the polysiloxane surface characteristics even after water rinsing, friction cycling, long-term storage, chemical treatment, or immersion treatment.

9. The application of the solvent-induced dual-end anchored durable polysiloxane coating of claim 8 in low-adhesion, anti-fouling, self-cleaning, low-friction, erosion-resistant, transparent anti-fouling surfaces.

10. The application as described in claim 9, characterized in that, The coating is used on photovoltaic glass, solar module covers, architectural glass, vehicle windows, display screen covers, sensor windows, transparent protective films, polymer films, polymer pipes, polymer sheets, fluid transport pipelines, microfluidic devices, ship surfaces, or antifouling component surfaces.